Ethics in engineering - Martin, Mike. ([S.l.] : McGraw-Hill Higher Education, 2004)
Now in its fourth edition, Martin and Schinzinger's Ethics in Engineering provides an introduction to the key issues in engineering ethics, taking account of both specific organizational contexts and broader technological trends. Current and thorough, it promotes critical thinking and discussion about moral and ethical issues that engineers face. The up-to-date content provides real world examples and cases and, by offering a framework for understanding ethical dilemmas within engineering, prepares readers for issues they will confront in their careers.
Import.